Logoterapi sebagai Upaya Peningkatan Kesejahteraan Psikologis pada Anak Pengidap Kanker - Fikriyatul Mufidah; Qurrota A’yuni Fitriana; Bakhrudin All Habsy (INDO PUBLISHING, 2026)
A cancer diagnosis in children not only impacts physical decline but also triggers psychological and existential distress that leads to a decline in psychological well-being. This study aims to determine the effectiveness of logotherapy interventions using play as a medium in improving the psychological well-being of children with cancer. The research design was pre-experimental with a one-group pretest-posttest design. The research instrument was independently constructed based on the dimensions of psychological well-being by Carol Ryff's theory. The logotherapy intervention was implemented for 1 month and implemented in a group form with a total of 4 children (N=4) with cancer as participants. Participants in the study were selected using a purposive sampling technique. The results of the study showed a significant increase in the average score of psychological well-being from 38.5 in the pre-test to 72.8 in the post-test (t = -7.49; p = 0.005 (p < 0.05). The results of the study prove that play-based logotherapy is effective in improving the psychological well-being of children with cancer. The main function of this intervention is to help children realize the meaning of their lives that chronic illness does not prevent them from rising to achieve their desires, as well as providing a group space for mutual support. These findings emphasize that medical treatment for children with cancer must be accompanied by psychological interventions to support the patient's overall quality of life.